ÎNVĂȚĂMÂNTUL SUPERIOR DIN REPUBLICA MOLDOVA: PROVOCĂRI ȘI PERSPECTIVE - Diaconu, Tatiana (CEP USM, 2022)
One of the key challenges facing the higher education system in the Republic of Moldova today is the relatively low number of students in universities. Statistics show that the number of students has decreased considerably over the last 15 years by about 53,19% overall, and for those enrolled by about 37,74%, also causing a shortage of students in the most vulnerable specialties, such as chemistry and mathematics, which subsequently had serious consequences on the labour market. Therefore, the shortage of students was and is caused by the phenomenon of students emigrating to other foreign countries. The main factors behind the decision of students to emigrate from the Republic of Moldova are: low salaries and lack of jobs, poor quality of life or the futility of establishing a desired career, etc.
Keywords: higher education; student; management; labor market; emigration